Divertem-se então à sua maneira : festas e morte na Irmandade de Nossa Senhora do Rosário e São Benedito, Florianópolis (1888 a 1940) - Rascke, Karla Leandro (2013)
This work presents considerations about the experiences of the brothers and sisters active in the Brotherhood of Our Lady of the Rosary and Saint Benedict, in Florianópolis/SC at the turn of the nineteenth to the twentieth. We propose to use as sources, memories recorded in written documents and photographs that reveal looks and performances in which we can infer expressions of their cultural traits and you live. We intend to understand the impact that social changes stemming from the abolition of slavery, the installation of the Republic and his works/hygienist reforms, Romanization clerical and coming of Germanic priests to Santa Catarina, had this Brotherhood, interfering in their forms of organization, expression cultural spaces of sociability and social visibility of African descent in the city of Florianópolis. We returned attention to the festivities in honor of the patron saints, being the feast and procession endowed with much preparation, decorations, bells and music, and to care for the dead, in order to provide a death rituals with all worthy and many masses for souls